Fast spiral-scan atomic force microscopy - Mahmood, Iskandar Al-Thani; Moheimani, S.O. Reza (IOP Publishing, 2009)
In this paper, we describe a new scanning technique for fast atomic force microscopy. In this method, the sample is scanned in a spiral pattern instead of the well established raster pattern. AÂ spiral scan can be produced by applying single frequency cosine and sine signals with slowly varying amplitudes to the x -axis and y -axis of an atomic force microscope (AFM) scanner respectively. The use of the single tone input signals allows the scanner to move at high speeds without exciting the mechanical resonance of the device and with relatively small control efforts. Experimental results obtained by implementing this technique on a commercial AFM indicate that high-quality images can be generated at scan frequencies well beyond the raster scans.